Analisis Kepuasan Pelanggan dalam Rangka Strategi Pemasaran Non-Tender PT Surveyor Indonesia (Persero) Cabang Surabaya - Arifin, Mahfud; Syairudin, Bambang; Achmadi, Fuad (Jurnal Bisnis dan Keuangan, 2018)
This study begins with collecting 73 samples taken with random sampling method from 266 SISUB’s customer. Variable questionnaire covers components and service quality components of the marketing mix. After analysis of data questioner, obtained for value an interest in the things that are desired by customers with average score 3.562. For the average perceived value obtained 3.493. Furthermore, by exposing data in the Cartesian diagram using Importance Performance Analysis (IPA) is known of position the quality of service that has been provided and there are 6 (six) things to be fixed in SISUB services. Framing of Matrix House of Quality (HOQ) is performed as a basicQuality Function Deployment (QFD) which is a method of design in determining the development of quality improvement measures of performance to satisfy customers. Preparation of HOQ carried out through Focus Group Discussion (FGD), the result is expected to improve performance in supporting the Customer Relationship Management (CRM).